2005
DOI: 10.1158/1055-9965.epi-04-0778
|View full text |Cite
|
Sign up to set email alerts
|

The E211 G>A Androgen Receptor Polymorphism Is Associated with a Decreased Risk of Metastatic Prostate Cancer and Androgenetic Alopecia

Abstract: The androgen receptor (AR) gene encodes a transcription factor, which mediates androgen action in target tissues, including the prostate. Prostate cancer is androgen dependent, implicating AR in susceptibility to this male condition. Male pattern balding, androgenetic alopecia, has recently been associated with prostate cancer, suggesting shared androgen pathways. The CAG and GGC repeats in the AR have been studied extensively as markers of prostate cancer susceptibility, with inconclusive findings, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 27 publications
3
45
0
1
Order By: Relevance
“…Our finding is in agreement with two previous studies, which reported lower risk of metastatic prostate cancer (19) and an overall decreased risk of prostate cancer (34) in men with the rs6152 A-allele, which is strongly linked with the A-allele of the SNP used in current study. Other studies did not find this association with prostate cancer (35,36), but these study populations were of multiethnic origin, which may have blurred the results.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding is in agreement with two previous studies, which reported lower risk of metastatic prostate cancer (19) and an overall decreased risk of prostate cancer (34) in men with the rs6152 A-allele, which is strongly linked with the A-allele of the SNP used in current study. Other studies did not find this association with prostate cancer (35,36), but these study populations were of multiethnic origin, which may have blurred the results.…”
Section: Discussionsupporting
confidence: 94%
“…One synonymous variant, E213 (rs6152G>A), is located between the two polymorphic CAG and GGN tracts. This variant has been linked to androgenetic alopecia in Caucasian populations, where the minor allele (rs6152A) in these populations was associated with a decreased risk (18)(19)(20). In a previous EMAS analysis, carriers of the rs6152A variant were also found to have significantly lower estradiol levels than those with rs6152G (21).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, AR is highly expressed in dermal papilla cells from beard, another site containing androgen-sensitive hair follicles, based on immunostaining [20] and RT-PCR [10]. From genetic aspects, genetic variability in a 1 Mb region within and centomeric to AR is reportedly associated with AGA at a significant level [23] and E211 G > A AR polymorphism is found to be associated with a decreased risk of AGA [24].…”
Section: Androgen Receptor (Ar)mentioning
confidence: 99%
“…1). The tag SNP selection procedure was 'forced' to include the following additional SNPs on the basis of (i) the previous association findings of our own or other groups, or (ii) their location in coding regions of the AR and EDA2R genes: rs2497938, 7 rs12396249, 7 rs1041668, 7 rs6152, [2][3][4]8 rs1352015, 5 rs4827545, 5 rs1385699, 5 rs12558842 5 and rs9332971. We selected the polymorphic GGN repeat reported by Hillmer et al 3 as an additional marker to clarify its role in the pathology of AGA.…”
mentioning
confidence: 99%